SINTESIS FOAMING AGENT ASAM LAURAT SAWIT DAN KARAKTERISTIK SIFAT FISIKOKIMIA - Jihan Pradesi, Erliza Hambali dan Endang Warsiki (Jurnal Teknologi Industri Pertanian, 2017)
Synthesis of foaming agent was conducted by reacting fatty acid of vegetable oil and alkaline. In this study, the selected fatty acid consisted of palm oil as raw material; with NaOH and KOH as alkali materials. The factor observed was molar ratio of reactant added into reactor. This research was aimed to determine the best molar ratio to produce foaming agent from lauric acid, to know its physico-chemical propertie,; and to obtain the foaming agent performance. Statistical analysis result indicated that the alkali type and molar ratio exhibited significant influence on pH, viscosity, density, surface tension, contact angle, interfacial tension, foamstability, and emulsion stability. The best ratio was by 1 mol of lauric acid and 0.5 mol of KOH 30% w/w with  characteristics as followed test was performed at room temperature for 24 h, pH of 9.88, density of 0.9959 g/cm3, viscosity of 1.85 cP, surface tension of 3.14 dyne/cm, interfacial tension of 8.39 dyne/cm, and contact angle of 18.28o in the 10th minute (with initial angle of 73.99o). Foam and emulsion stability test were carried out and indicated that Na–laurate foaming agent showed higher performance than K–laurate.Keywords: alkali, foaming agent, lauric acid, palm oil